SMARTPHONE USE AND THE INSPIRA DIGITAL APP IN MATH CLASSES DURING REMOTE CLASSES - Andrade, Emanuel Adeilton O.; de Assis de O. Andrade, Francisco; Dalva da Silva Santos, Maria (Journal of Interdisciplinary Debates, 2021)
This work highlights the use of the digital inspiration application in mathematics classes as a pedagogical tool, as an explanatory/demonstrative instrument of the concepts and elements of geometric solids in the 6th grade classes, at the Professora Maura de Medeiros Bezerra Municipal School – Macau/RN. The purpose of this application was to expand the possibilities of learning in the Hybrid format in the pandemic period as an inverted classroom methodology.